UX-Tips: A UX evaluation technique to support the identification of software application problems - Marques, Leonardo; Matsubara, Patrícia; Nakamura, Walter; Wiese, Igor; Zaina, Luciana; Conte, Tayana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2019)
User Experience (UX) is a quality attribute that plays an important role in the quality of software applications, as it addresses users' feelings about a given product. Thus, evaluating the UX is essential to improve its quality. However, most UX evaluation techniques limit to indicate whether the UX was positive or negative, which makes it challenging to identify what must be corrected by the software development team. This paper presents UX-Tips (User eXperience for Interactive ProductS), a technique developed to deal with this limitation, whose main objective is to allow the identification of problems related to UX. We also present two empirical studies conducted to evaluate UX-Tips. In the first study, we assessed the feasibility of the technique concerning its primary goal. In the second study, we compared the performance of UX-Tips with a similar technique. The results showed that UX-Tips allowed the subjects to indicate whether the UX was negative, and the specific problems they detected. It also allowed more effective and efficient evaluations, in addition to being considered easier to use. In practice, UX-Tips enable the software development team to identify the problems that impair users' experience, which should be fixed in order to provide a good UX.